KAJIAN EMPLOYEE ENGAGEMENT DI BALAI DIKLAT APARATUR KEMENTERIAN KELAUTAN DAN PERIKANAN - Yudistira Adi Nugroho (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Organizations need employees who not only have a high level of satisfaction at work, but also have a high commitment, are involved in running the organization's business and have high loyalty and have a sense of ownership in the organization or have a level of citizenship towards the organization. This study aims to examine employee engagement at the Apparatus Training Center of the Ministry of Maritime Affairs and Fisheries. Through this study, it can also provide an overview of aspects that need to be improved by the organization in order to increase employee engagement. For research purposes, the method used in this research is descriptive quantitative. Descriptive research is used to describe or analyze the condition of each variable. While quantitative is intended to analyze the results of data collection and processing. The technique used to analyze employee engagement of the Apparatus Training Center of the Ministry of Maritime Affairs and Fisheries is based on the results of filling out a questionnaire with a Likert scale range. The results of the study indicate that the average employee of the Ministry of Maritime Affairs and Fisheries Apparatus Training Center is in the engaged category. This means that all employees have high enthusiasm, commitment, loyalty and dedication to the organization.